Features of Regulation of Work of Workers of the Religious Organization - Tatiana Mihailovna Ponomaryova (Сибирское юридическое обозрение, 2011)
The article deals with labor relations of employees in religious organizations. Specificity of activity of religious organizations is reflected in the content of the labor contract of employees. The author analyzes characteristics of subjects of the labor contract in the religious organization. The author studies peculiarities of conclusion, change and termination of the labor contract, as well as specificity of working schedule of employees in a religious organization.